Arcaína reverte a preferência condicionada por lugar induzida por morfina em camundongos - Tomazi, Lediane (2014)
The morphine addiction is a chronic disease that involves biological, cognitive and behavioral changes developed after repeated and compulsive drug use. Even after long periods of abstinence relapses occur to users, especially when faced with situations that resemble the use thereof. The protocol of conditioned place preference (CPP) has been one of the most widely used experimental models to measure the positive reinforcing effects (conditioned place preference) and negative (conditioned place aversion) of several drugs, including morphine. Studies show that antagonists of the N-methyl-D-aspartate (NMDA) block morphine-induced CPP, suggesting that this receptor is involved in the effects of morphine. Since polyamines act at the NMDA receptor, spermidine (SPD) positive allosteric modulating shape and arcaine acting as an antagonist of the polyamine site on this receiver, the purpose of this study the effect of polyamines on the preference induced conditioned place was to evaluate morphine. Adult male Swiss mice were pre-conditioned once a day for 15 minutes for two consecutive device in the CPP, the next day days were subjected twice daily for conditioning sessions with different drugs and protocols for four consecutive days. Twenty-four hours after the last conditioning session the animals were subjected to the test. The CPP score was calculated for the time spent in the compartment paired with the drug on test day, minus the time spent in the same compartment on the second day of the preconditioning. The results of this study showed that morphine (2.5-10 mg/kg, ip) induced CPP, but not aversion induced conditioned place aversion, the SPD (3-30 mg/kg, ip) and arcaine (0.3-3 mg/kg, ip) did not preferably nor induced conditioned place aversion. However, arcaine (3 mg/kg) administered 15 min before morphine (5 mg/kg) attenuated the pre-training acquisition of morphine-induced PCL. The arcaine (3 mg/kg) administered immediately after conditioning with morphine (5 mg/kg) blocked morphine induced PCL. Also, arcaine (3 mg/kg) administered 30 min pretest blocked morphine induced expression CPP. Furthermore, the effect of arcaine on attenuate the effect of morphine was prevented by the administration of SPD before conditioning, but was not reversed by postconditioning pre-test administration and SPD. These data indicate that arcaine blocks the rewarding effect of morphine and arcaine suggests that it could be a therapeutic target in the development of drugs to treat addiction to morphine.